Validation of an instrument to measure the use of resources associated with ICT in higher level institutions - Fitch Osuna, Miguel Angel (UNIVERSIDAD DE SONORA, 2019)
The purpose of this study is to validate a series of indicators that allow us to evaluate the use of technological resources in higher level institutions, in this case focused on the degree of Architecture and Industrial Design. The sample corresponds to 173 students who were about to present their term exam. To validate the model, a system of structural equations has been used, having 7 constructs, which we will refer to as: Access to ICT resources, digital competences of the student, general competencies of the teacher, digital competences of the student, student attitudes towards ICT, self-efficacy perceived and use of ICT resources. Interested universities can use this instrument to diagnose and improve the characteristics of both their human resources and technological infrastructure. The results obtained show the confidence of being a valid and reliable instrument for the measurement of the study variables.